Kepuasan Pelajar Terhadap Kualiti Perkhidmatan Jabatan Bendahari Universiti Utara Malaysia - Zulkifli, Omar (2011)
Quality is an ongoing process of building and sustaining relationships between organization and the customers. It was a function through services organization to fulfill unpredicted need and want of the customers. Customers' satisfaction depends on the service quality that they received from the service provider. Failure to fulfill customer's expectation and satisfaction will lead to bad impressions to the organization itself in the long term. The main purpose of this study is to determine student's satisfaction toward service quality at Bursar Department of Universiti Utara Malaysia (UUM). Three hundred and seventeen (317) respondents which are UUM's main campus students participated in this survey. Questionnaires are being used in this survey and the analyses of findings analysis are based on descriptive statistics. The findings showed that four (4) dimensions of quality service namely Assurance, Reliability, Tangibles and Responsiveness have significant relationship with an overall service quality while no significant relationship is evidence for the Empathy dimension. Based on Multiple Regression Model, the finding showed that only Assurance and Reliability have strong relationship to overall services quality at Bursar's Department of UUM. These outcomes are useful for Bursar's Department in planning their strategy toward in improving the quality of services in future.